Psychiatric disorders prior to amyotrophic lateral sclerosis - Turner, M; Goldacre, R; Talbot, K; Goldacre, M (Wiley, 2016)
It is recognized that neuropsychiatric conditions are over-represented in ALS patient kindreds and psychiatric symptoms may precede the onset of motor symptoms. Using a hospital record linkage database, hospitalization with a diagnosis of schizophrenia, bipolar disorder, depression or anxiety was significantly associated with a first diagnosis of ALS within the following year. This is likely to specifically reflect the clinicopathological overlap of ALS with frontotemporal dementia. A diagnosis of depression was significantly associated with a first record of ALS five or more years later, in keeping with growing evidence for major depressive disorder as an early marker of cerebral neurodegeneration.